Ground Joint Debugging Test System of Electric Propulsion System for Ocean Trawler - LU Xiulong; ZHAO Jianwei; CHENG Hao; WU Shuangyi; HE Wulin (Kongzhi Yu Xinxi Jishu)
There are no standards of ground joint debugging test method for ship electric propulsion system at present, and different test items apply to different ship electric propulsion system projects, which give rise to uncertainty of adequate validation. It took as an example the electric propulsion system of an ocean trawler, and proposed a ground joint debugging test system, studied test items of the proposed system through the analysis, and presented the corresponding testing curves. The proposed test system can also be applied to other ship electric propulsion system, providing a reference for the design and manufacture of test system for ship electric propulsion system.